ENVIRONMENTAL PROBLEMS ITS EFFECTS AND APPLICABLE METHODS - Ahmed, NikhatParveen (International Journal of Research -GRANTHAALAYAH, 2015)
HOW PSYCHOLOGY DEAL WITH ENVIRONMENT? "Environmental Psychology is field of study that examines the inter relationship between environment and human affect cognition and behaviour" (Bechtel &chorchman 2002, Gilford 2007)